#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.

Click to Chat

1800-1023-196

+91 7353221155

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# x(y+z-x)/logx = y(x+z-y)/logy = z(x+y-z)/logz  so show that,                  xyyx = yzzy = zxxz ................ ## 1 Answers

8 years ago

nice question but cracked let the given be equal to k-

 x(y+z-x)/logx = y(x+z-y)/logy = z(x+y-z)/logz    =k   or, logx=x(y+z-x)/k, multiplying by y on both sides, we get-   ylogx=xy(y+z-x)/k      ....(1) also, multiplying both sides by z we get-     zlogx=zx(y+z-x)/k   ........(2)   and, logy=y(x+z-y)/k, multiplying both sides by x, we get-      xlogy=xy(x+z-y)/k    .......(3) also, multiplying both sides by z we get-     zlogy=zy(x+z-y)/k   ...........(4)   and, logz=z(x+y-z)/k, multipying both sides by y, we get-        ylogz=yz(x+y-z)/k    .......(5) also, mulitplying both sides by x we get-     xlogz=xz(x+y-z)/k    ..........(6)
 adding 1 and 3, we have- log(x^y)(y^x)=xyz/k
 adding 4 and 5, we have- log(y^z)(z^y)=xyz/k

adding 2 and 6, we have- log(z^x)(x^z)=xyz/k

comparaing the RHS of above and removing log, we have-

(x^y)(y^x)=(y^z)(z^y)=(x^z)(z^x)

Hence proved. AJ

## ASK QUESTION

Get your questions answered by the expert for free